Hepato-biliary profile of potential candidate liver progenitor cells from healthy rat liver - Maerckx, Cédric (Baishideng Publishing Group Co., Limited, 2012)
AIM: To evaluate the presence of progenitor cells in healthy adult rat liver displaying the equivalent advanced hepatogenic profile as that obtained in human. METHODS: Rat fibroblastic-like liver derived cells (rFLDC) were obtained from collagenase-isolated liver cell suspensions and characterized and their phenotype profile determined using flow cytometry, immunocytochemistry, reverse transcription polymerase chain reaction and functional assays. RESULTS: rFLDC exhibit fibroblastoid morphology, express mesenchymal (CD73, CD90, vimentin, α-smooth muscle actin), hepatocyte (UGT1A1, CK8) and biliary (CK19) markers. Moreover, these cells are able to store glycogen, and have glucose 6 phosphatase activity, but not UGT1A1 activity. Under the hepatogenic differentiation protocol, rFLDC display an up-regulation of hepatocyte markers expression (albumin, tryptophan 2,3-dioxygenase, G6Pase) correlated to a down-regulation of the expression of the biliary marker CK19. CONCLUSION: Advanced hepatic features observed in human liver progenitor cells could not be demonstrated in rFLDC. However, we demonstrated the presence of an original rodent hepato-biliary cell type.